Space Trumps Time When Talking About Objects. Issue 3 (21st March 2019) - Griffiths, Debra; Bester, Andre; Coventry, Kenny R.
Abstract: The nature of the relationship between the concepts of space and time in the human mind is much debated. Some claim that space is primary and that it structures time (cf. Lakoff & Johnson, 1980) while others (cf. Walsh, 2003) maintain no difference in status between them. Using fully immersive virtual reality (VR), we examined the influence of object distance and time of appearance on choice of demonstratives ( this and that ) to refer to objects. Critically, demonstratives can be used spatially ( this/that red triangle ) and temporally ( this/that month ). Experiment 1 showed a pattern of demonstrative usage in VR that is consistent with results found in real‐world studies. Experiments 2, 3, and 4 manipulated both when and where objects appeared, providing scenarios where participants were free to use demonstratives in either a temporal or spatial sense. Although we find evidence for time of presentation affecting object mention, the experiments found that demonstrative choice was affected only by distance. These results support the view that spatial uses of demonstratives are privileged over temporal uses.